Improving food security? Setting indicators and observing change of rural household in Central Sulawesi - Dewi Nur Asih; Stephan Klasen (Forestry Faculty, Universitas Hasanuddin, 2017)
Household food security is a critical issue for Indonesia, which is investigated in this study. Many of rural household in Indonesia depends on agricultural sectors and facing challenges of global warming that threatening food security and poverty alleviation in the country. We use panel data at the household level for a sample of households living in Central Sulawesi at the rainforest margin in Indonesia. For the purpose of this study, we apply principal component analysis to develop an indicator of food security and used the index in determining the household’s condition to be persistent food secure or insecure. The findings present the fact that over the period the household’s food security in the study area has changed to better food condition. The number of people who are food insecure has declined by 23.73 % over the year. However, the results suggest that public services on health, education and infrastructure need to be strengthened, investments in access to credit and off-farm employment policies, as well as insurance programs on social protection and disaster management, need to be developed.